Unaffected by Working Capital, Liquidity, and Solvency Profitability: Evidence from Indonesia - Rahman, Abdul; Sutisna, Entis (Advances: Jurnal Ekonomi & Bisnis, 2023)
Purpose: This study examines the impact of Working Capital Turnover (WCT), Current Ratio (CR), and Debt-to-Asset Ratio (DAR) on Return on Assets (ROA) in food and beverage companies listed on the Indonesia Stock Exchange (IDX) to understand their financial performance. Research Design and Methodology: The study uses a quantitative approach with purposive sampling, selecting ten primary food and beverage manufacturing companies listed on IDX. Secondary data from corporate financial reports are analyzed using multiple linear regression and statistical tests, including descriptive analysis, normality tests, multicollinearity tests, heteroscedasticity tests, t-tests, and F-tests. Findings and Discussion: The results indicate that WCT has a negative and insignificant effect on ROA, CR has a negative and significant impact, and DAR has a positive and insignificant effect. However, simultaneous testing confirms that WCT, CR, and DAR collectively have a significant impact on ROA, emphasizing the role of financial management in profitability. Implications: These findings offer financial managers and investors valuable insights into optimizing working capital, liquidity, and financial leverage to enhance profitability. Businesses should balance liquidity and debt management to maximize returns. Future research can explore additional financial metrics across different industries for broader insights.